Kemampuan Komunikasi Matematis Ditinjau dari Gender Siswa - Hilda Hakim; Leni Agustina Daulay; Maya Listari (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2021)
One of the problems the important thing in learning Mathematics in Indonesia today is the development of students' mathematical communication skills. Communication development is one of the objectives of learning Mathematics and is one of the competency standards for Mathematics graduates. In Indonesia, the assessment of communication skills includes students' ability to present and interpret Mathematical ideas orally, in writing or in demonstration. Indicators of communication skills in written form are (1) drawing; (2) mathematical expressions; (3) written texts. Differences in gender (gender) certainly cause psychological differences in learning, so that male and female students certainly have differences in the ability to understand and communicate. The type of research used is quantitative research with a descriptive approach. The results showed that basically female students were more accurate and detailed while male students were more critical in various interpretations. There is a difference between the average scores obtained by male students and female students. This shows that the mathematical communication ability of female students is better than that of male students, with an average score of 83.1 for female students compared to an average score for male mathematical communication of 75.7 with a difference of 7.4%.